2023
DOI: 10.3390/cancers15061631
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of [99mTc]Tc-maSSS-PEG2-RM26, a Bombesin Analogue Antagonistic to Gastrin-Releasing Peptide Receptors (GRPRs), for SPECT Imaging of GRPR Expression in Malignant Tumors

Abstract: The gastrin-releasing peptide receptor (GRPR) is overexpressed in prostate cancer (PCa) and in hormone-driven breast cancer (BCa). The aim of this phase I clinical trial was to evaluate safety, biodistribution, and dosimetry after the administration of the recently developed GRPR-targeting antagonistic bombesin analogue [99mTc]Tc-maSSS-PEG2-RM26 in PCa and BCa patients. Planar and whole-body SPECT/CT imaging was performed in six PCa patients and seven BCa patients 2, 4, 6, and 24 h post the intravenous adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The effective dose was calculated to be 0.00423 Sv/GBq, Obviously, upscaling from mice to humans is associated with multiple uncertainties ( 32 ). On the other hand, our upscaling of dosimetry of a bombesin-based imaging probe [ 99m Tc]Tc-maSSS-PEG2-RM26 (effective dose 0.00349 mSv/MBq) ( 33 ) showed to be in a reasonably good agreement with clinical data (0.0044 ± 0.0006 mSv/MBq) ( 34 ). As a first approximation, we compared the upscaling to humans of absorbed doses in different organs calculated for [ 177 Lu]Lu-BQ7876 in this study and for [ 177 Lu]Lu-PSMA-617 ( 35 ).…”
Section: Discussionmentioning
confidence: 70%
“…The effective dose was calculated to be 0.00423 Sv/GBq, Obviously, upscaling from mice to humans is associated with multiple uncertainties ( 32 ). On the other hand, our upscaling of dosimetry of a bombesin-based imaging probe [ 99m Tc]Tc-maSSS-PEG2-RM26 (effective dose 0.00349 mSv/MBq) ( 33 ) showed to be in a reasonably good agreement with clinical data (0.0044 ± 0.0006 mSv/MBq) ( 34 ). As a first approximation, we compared the upscaling to humans of absorbed doses in different organs calculated for [ 177 Lu]Lu-BQ7876 in this study and for [ 177 Lu]Lu-PSMA-617 ( 35 ).…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, it also showed a biodistribution profile suitable for GRPR-positive prostate cancer imaging and acceptable dosimetry estimations when tested on animal models [20]. Recently, [ 99m Tc]Tc-maSSS-PEG2 -RM26 was studied in a phase I clinical study, and it was demonstrated that single injections of this agent were well tolerated and were associated with low absorbed doses in healthy organs and tissues [27]. The agent was tested for SPECT imaging of prostate and breast cancer lesions, and a number of primary tumors of both origins, as well as breast cancer lymph node metastases, which were visualized shortly after administration (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since the position of the kidneys is well defined, the use of SPECT/CT makes it possible to distinguish the high radioactivity accumulation in the kidneys from other organs and tissues. In contrast, radioactivity in the gastrointestinal tract in the case of [ 99m Tc]Tc-BQ0411 and [ 99m Tc]Tc-BQ0412 is more problematic [37]. This can lead to false-positive findings because of the occasional formation of volumes with a high activity concentration in the content of the gastrointestinal tract.…”
Section: Organ [ 99mmentioning
confidence: 99%